Análisis de las Propiedades Psicométricas de una versión autoaplicada de la Escala de Gravedad de Síntomas de Estrés Postraumático en una muestra de Bogotá - Rodríguez Castellanos, Pedro Germán (Universidad Antonio Nariño, 2024)
The present work details the Analysis of the Psychometric Properties of a self-applied version of the Post-Traumatic Stress Symptom Scale in a sample of Bogotá, in a group of normative (common) people, of 303 people. The data showed a structure with a KMO of 0.94 that reveals the presence of relational factors of variables; for the study of reliability, a value of 0.887 was found, which is within the coefficient range reached by the original Spanish test of (0.89). The type of distribution in the sample was also evidenced. The cut-off points for the 75th percentile coincide with the Spanish sample and the local sample. The total Cronbach's alpha was 0.96; which allows it to be located in the range of excellent internal consistency according to the classification proposed by George and Mallery (2003).